Examination of the patients applying to the physical therapy unit of a hospital due to low back pain - Edibe Pirincci; Ferit Kaya; Eyyup Demirpolat (SERNEV, 2018)
Introduction: This studyanalyzes factors influencing low back pain in patients admitted to the physiotherapyunit of an education and research hospital. Methods: The studysample included 102 patients who applied to the physiotherapy unit andvolunteered to join the study. The data were collected using a 23-itemsquestionnaire created by the authors based on a review of the literature. Thedata were entered into the SPSS Program For comparisons, p values below 0.05were deemed to be statistically significant. Results: The meanage of the participants was 46.7±14.4 years. By occupation, low back pain wasmost common among housewives. Of the patients who suffered from lower backpain, 57.8% were overweight or obese. Of those experiencing lower back pain,73.5% were standing for long time periods, and 67.6% were lifting heavy loads.Of the patients, 69.6% had lower back pain in their families, and 29.4% of thefamily members with lower back pain were their mothers.Of the patients, 70.6% received drug therapy for the pain. The frequencyof low back pain among patients who did not receive drug therapy was higherthan that of the patients who received pain medications (p lt;0.05). Of thepatients who had low back pain attacks 11 times or more in a year, thepercentage of smokers was 66.7%, while this rate was 35.7% among nonsmokers(p lt;0.05). The increase in low back pain with body mass index was notstatistically significant (p gt;0.05). Conclusion: Patientsapplied to the hospital due to low back pain report lifting heavy loads orprolonged standing. Smoking increases the frequency of low back pain. Patientswith low back pain also tend to have family members with the condition. Withappropriate measures to reduce risk factors, the frequency of low back pain,which hinders daily life activities, can be reduced.